Reshoring as a form of deglobalisation : the US automotive industry - Barták, Martin; Čajka, Radek, 1983-; Černá, Iveta, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This bachelor thesis explores the reshoring phenomenon in the US automotive industry against the backdrop of increasing deglobalisation. It explores strategic decisions by major US automakers, specifically Ford Motor Company and General Motors, to relocate production back to the United States due to the turbulent economic conditions in recent times, such as the Great Financial Crisis in 2007–08, increasing geopolitical tensions, and the COVID-19 pandemic. Through a comprehensive literature review and a qualitative analysis of industry reports and academic studies, the thesis identifies the multifaceted drivers of reshoring. Findings indicate that reshoring in the US automotive sector is driven not only by traditional cost and efficiency considerations but also by US government incentives, consumer preferences, supply chain resilience, sustainability concerns, and technology advancements. This phenomenon impacts global supply chains and the competitive dynamics of the automotive industry, not only in the US. The paper underscores reshoring as both a catalyst and a symptom for deglobalisation.
Vedoucí práce: Radek Čajka
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses